Extremum Seeking Control for Power Output Maximization of Proton Exchange Membrane Fuel Cell using Sliding Mode - Junsheng Jiao (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Due to the nonlinear P-I characteristic of fuel cells, it is very important to implement a maximum power point tracking (MPPT) controller for practical applications. Based on analyzing the output characteristics of fuel cell power system, this paper presents extremum seeking sliding mode control method for MPPT of fuel cell power system under variable temperature and water content conditions. The approach is a combination of the extremum seeking and sliding mode methods. The simulation results show that the approach improves clearly the tracking efficiency of the maximum power available at the output of the fuel cell modules. The new method reduces the oscillations around the MPP, which has shown better performances. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.2976